2022
DOI: 10.13059/racef.v13i2.858
|View full text |Cite
|
Sign up to set email alerts
|

Personal Values and the Use of Sources of Guidance at Work: A Comparison Between the United States and Brazil

Abstract: The objective of this research was to test statistically significant correlations between personal values and employee’s use of sources of guidance when dealing with different events at work, comparing the United States and Brazil. 220 employees from a Brazilian university and 166 employees from an American university filled out a paper-and-pencil questionnaire comprised of two previously-validated scales. Based on the theoretical review, 8 hypotheses were raised to be empirically tested. The findings have pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The discussion showed that some of these differences were compatible with national cultural characteristics. Athayde et al (2022a) explored statistically significant correlations between personal values and employees' use of sources of guidance when dealing with different work events in the United States and Brazil. In the United States, the authors found correlations between high scores in the value Power-Dominance and less reliance on superiors.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The discussion showed that some of these differences were compatible with national cultural characteristics. Athayde et al (2022a) explored statistically significant correlations between personal values and employees' use of sources of guidance when dealing with different work events in the United States and Brazil. In the United States, the authors found correlations between high scores in the value Power-Dominance and less reliance on superiors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Authors who empirically compared the use of Sources of Guidance in Brazil and The United States in light of national cultural characteristics. Athayde, Torres, and Thomason (2022a) Authors who empirically tested correlations between personal values and the use of sources of guidance at work. Athayde, Torres, and Thomason (2002b) Authors who empirically tested the influence of personal values and dark personality traits on the use of sources of guidance at work.…”
Section: Athayde and Torres (2022)mentioning
confidence: 99%